Factors Influencing Compliance with Ethical Standards Among Radiographers in Selected Health Facilities in Greater Accra Region - Osei-Bonsu, A.G. (University of Ghana, 2024)
Introduction: Radiographers play a critical role in helping diagnose and treat medical conditions, and their responsibilities require a high degree of technical expertise, attention to detail, and a commitment to patient care. However, non-compliance with ethical standards can significantly impact the quality of patient care, particularly concerning imaging standards. Current literature on radiographers’ adherence to ethical standards is limited, highlighting a need for further exploration in this area. Methods: The study utilised a cross-sectional analytic design, conducted in selected health facilities in the Greater Accra Region, involving 80 diagnostic radiographers. Data collected were analysed using STATA Version 16. Breaches in ethical standards were reported as means and standard deviations (SD). The association between socio-demographic factors and compliance with ethical standards was assessed using Fisher’s exact test. Additionally, factors influencing compliance to ethical standards were assessed using simple and multiple logistic with statistical significance determined at a p-value of less than 0.05. Results: The majority of participants (76%) demonstrated good knowledge of existing ethical standards, while a similarly high percentage (79%) of radiographers exhibited high level of compliance with ethical standards. No breaches in ethical standards were reported concerning the scope of practice (mean=1.44, SD=0.80), commitment to practice (mean=1.41, SD=0.85), commitment to profession (mean=1.37, SD=0.86), and safety (mean=1.47, SD=0.85). After adjusting for confounding variables, a significant association was found between knowledge of existing ethical standards and compliance with these standards among radiographers [AOR=6.29, CI= (1.51-26.13), p=0.011]. Conclusion: The majority of radiographers demonstrated a strong understanding of existing ethical standards and exhibited high levels of compliance with these standards. A significant association was found between knowledge of ethical standards and compliance, indicating that radiographers with good knowledge were more likely to adhere to ethical standards. To sustain this high level of ethical compliance, it is essential to continually remind radiographers of ethical standards through in-service trainings and orientation of new radiographers.
MPH
Keywords: Radiographers; medical conditions; ethical standards; patient care